INOVASI PROGRAM EKSTRAKURIKULER OLEH KEPALA SEKOLAH UNTUK MEMBANGUN KECAKAPAN ABAD 21 PADA SISWA - Yinarti Hida; Novianty Djafri (Tadbir: Jurnal Manajemen Pendidikan Islam, 2024)
This study aims to research the innovation of extracurricular programs carried out by school principals to build 21st-century skills in students at SMP Negeri 2 Limboto. Extracurricular program innovation It is considered a strategy to develop the skills required by students in the 21st-century era, such as creativity, collaboration, communication, and problem-solving skills. This study uses a qualitative approach by analyzing the innovation of extracurricular programs implemented by the principal of SMP Negeri 2 Limboto. The study results show that extracurricular program innovations carried out by school principals have a significant role in building 21st-century skills in students. Various innovatively designed extracurricular programs can help students develop critical, creative, communicative, and collaborative skills. In addition, the innovation also provides a space for students to explore their interests and talents outside of the formal curriculum. However, it was found that there were several obstacles related to the program's implementation, namely budget limitations, inadequate facilities, and lack of special training for teachers. These constraints hinder the effectiveness and sustainability of extracurricular programs designed to meet the needs of 21st-century skills. The implication of the results of this study is the need for further support for school principals in developing and implementing extracurricular program innovations relevant to the demands of 21st-century proficiency needs.